Multimodal Semiotic Resources in Online Learning Environments: Meaning-Making from an Applied Linguistics Perspective - Rizqan Mahardika Putrawan; Nadira Nadira (LIER: Language Inquiry & Exploration Review, 2026)
Purpose: This study examines the use of multimodal semiotic resources in online applied linguistics courses and their role in supporting meaning-making, comprehension, and collaborative learning. Subjects and Methods: The study involved 120 undergraduate applied linguistics students who engaged with text-based slides, video lectures, infographics, podcasts, and discussion forums. A convergent parallel mixed-methods design was employed. Quantitative data were collected through surveys, usage logs, and comprehension tests, while qualitative data were gathered via semi-structured interviews and observation of forum interactions. Descriptive statistics, Pearson correlation, and thematic analysis were used to analyze the data, and findings were integrated through triangulation. Results: Slides and video lectures were the most frequently used and highly rated resources, showing strong positive correlations with comprehension scores. Infographics and discussion forums facilitated summarization, reflection, and collaborative knowledge construction, whereas podcasts were less effective when used in isolation. Students who integrated three or more modalities achieved higher comprehension, highlighting the benefits of multimodal learning. Forum participation promoted peer-to-peer negotiation of meaning, metacognitive awareness, and self-directed learning. Conclusions: The integration of multiple multimodal resources significantly enhances comprehension and meaning-making in online learning. Effective online courses should balance structured guidance, interactive engagement, and diverse resources, positioning multimodal approaches as essential for fostering collaborative, reflective, and self-directed learning in applied linguistics education.